OPERATIONAL RISK MANAGEMENT OF SURABAYA MAIN NAVAL BASE V REPAIR AND MAINTENANCE FACILITY BASED ON ISO 31000 FRAMEWORK - Yunus Patabang; Suprayitno Suprayitno; Erpan Sahiri; I Made Jiwa (JOURNAL ASRO, 2019)
Surabaya Main Naval Base V Repair and Maintenance Facility is one of the work units under the auspices of the Indonesian Navy that is tasked with carrying out the maintenance and repair of all major weapons systems of the Indonesian Navy. In carrying out their duties Surabaya Main Naval Base V Repair and Maintenance Facility has a big challenge and even there are various kinds of risks to prepare all the Indonesian Armed Forces defense equipment in accordance with the demands of need. Therefore, in this research, risk management will be carried out at the Surabaya Main Naval Base V Repair and Maintenance Facility Operational based on the ISO 31000: 2018 framework. Based on this framework, risk management will be carried out, namely how to carry out risk assessments in the form of risk identification, risk analysis, and risk evaluation for all risks in the operational field. Enterprise Risk Management (ERM) is also used to carry out in-depth risk management processes. One method used to solve existing problems is to use the House of Risk (HOR) method, which is divided into two stages. Stage 1 HOR focuses on ranking the Aggregate Risk Potential (ARP) value and with the help of the Pareto diagram the cumulative ARP value is obtained to determine the risk event (risk agent) selected, which then requires treatment on a priority scale. The results of this HOR phase 1 are then included in HOR phase 2 to rank the most effective prevention measures based on costs and resources. From the results of the HOR phase 2, further brainstorming was carried out with the Surabaya Main Naval Base V Repair and Maintenance Facility in accordance with the actions chosen for preventive actions that could be immediately carried out.Keywords: House of Risk, Enterprise Risk Management, SNI ISO 31000: 2018.